Synthesis, Characterization and Anticonvulsant Activity of Novel Benzyl-6-Chloro Indole Carboxylate Derivatives (Journal of Basic and Applied Research in Biomedicine, 2022)
Indole is one of the most important heterocyclic compound, weak base, having varied biological activities and still of great scientific interest now a days. They are widely found in bioorganic and medicinal chemistry with application in drug discovery. In the present study some novel indole carboxylate derivatives were synthesized under green synthesis by microwave irradiation method according to the scheme. Methyl 6-chloro-1Hindole-5-carboxylate was treated with benzyl chloride in presence of CS2CO3 in dry DMF. Then methyl 1-benzyl-6-chloro-1H-indole-5-carboxylate was treated with oxalyl chloride in dry DCM and different secondary amines to get methyl 1-benzyl-6-chloro-3-[(N,N-dialkylamino)(oxo)acetyl]-1H-indole-5-carboxylates derivatives (IND-1 to IND-10). The synthesized newer indole carboxylate derivatives have been characterized by using elemental analysis, FT-IR, 1HNMR, 13C NMR spectroscopy and further supported by Mass spectroscopy. Purity of all the compounds has been checked on thin layer chromatographic plate and HPLC technique. All the synthesized compounds were evaluated for anticonvulsant activity by maximal electroshock method (MES) by using phenytoin as standard at a concentration of 30 mg/kg. The anticonvulsant effect of the newly synthesized compounds was assessed by absence or reduction of hind limb tonic extensor phase. Among the synthesized derivatives compounds IND-5 and IND-10 were found to be the most potent compounds in the series.